The effect of a comprehensive support program on the stress level of mothers in a neonatal intensive care unit - Esra Goral; Emine Geçkil (Tehran University of Medical Sciences, 2021)
Background & Aim: Parents of neonates hospitalized in the neonatal intensive care unit may experience a high level of stress. Although many approaches were applied for reducing their stress, however little is known about the effect of a comprehensive support program. The aim of this study is to investigate the effect of a comprehensive supportive program on maternal stress levels in a neonatal intensive care unit. Methods & Materials: In a quasi-experimental study, 62 mothers whose premature neonates were hospitalized in a neonatal intensive care unit, were selected and assigned into experimental and control groups. A comprehensive support program was applied for the mothers in the experimental group, whereas the mothers in the control group received the standard routine care. Data were collected and analyzed using SPSS software and the p-value was considered at P≤0.05.    Results: It was found that the maternal stress level in the experimental group (mean=2.95±.72) was significantly lower than those in the control group (mean=3.74±.82) (p=0.001). The effect magnitude of the change in the maternal stress level in the experimental group (d=1.20) was significantly higher than that of mothers in the control group (d=.36). Conclusion: A comprehensive support program is significantly effective in reducing maternal stress levels. So, it is highly recommended that nurses use these comprehensive approaches in practice and especially support mothers by facilitating interaction between parents experiencing similar problems. Further research can focus on the effect of group training on the stress level of mothers.